2014
DOI: 10.1071/sr13243
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in phosphorus concentrations when P fertiliser application is reduced or omitted from grazed pasture soils

Abstract: Many intensively managed soils contain phosphorus (P) concentrations greater than required for optimum production. Soils with P concentrations in excess of the agronomic optimum can have unnecessary losses of P that can adversely affect water bodies. Reducing excessive soil-P concentrations is important for the economic and environmental sustainability of intensive agriculture, such as the Australian dairy industry. However, little is known of decreases in extractable soil-P concentrations when P fertiliser ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Soils with high STP will meet crop P demands over a longer time period than soils with lower STP (Table 2). Declines in STP are initially rapid on very P-rich soils, and then decline more slowly as the labile P not extracted by STP replenishes P in the soil solution (McCollum 1991;Schulte et al 2010;Coad et al 2014;Johnston et al 2014;Fig. 1c).…”
Section: Strategy A: Drawdown Of Stpmentioning
confidence: 88%
See 1 more Smart Citation
“…Soils with high STP will meet crop P demands over a longer time period than soils with lower STP (Table 2). Declines in STP are initially rapid on very P-rich soils, and then decline more slowly as the labile P not extracted by STP replenishes P in the soil solution (McCollum 1991;Schulte et al 2010;Coad et al 2014;Johnston et al 2014;Fig. 1c).…”
Section: Strategy A: Drawdown Of Stpmentioning
confidence: 88%
“…Current STP methods also extract vastly different amounts and forms of soil P depending on the method used, and the role of rhizosphere processes in soil P acquisition is not adequately captured. Hence there are soils that can supply adequate Pi in solution even when STP is low (Herlihy et al 2004;Paris et al 2004), and Pi in the soil solution can decline faster than STP when P fertilizer is withheld (van der Salm et al 2009;Dodd et al 2012;Coad et al 2014). Thus, yield reductions from drawing down legacy P have been observed on some soils after relatively short periods, even though STP appears adequate, or even high (Table 2).…”
Section: Strategy A: Drawdown Of Stpmentioning
confidence: 96%
“…Third, the combination of elevated soil nutrient levels from fertilization and exotic species result in competitive exclusion of many native species that are adapted to lower nutrient soils (Bakker & Berendse, 1999;Prober et al, 2005;Seabloom et al, 2015). Soil nutrients, particularly phosphorus, may remain in grassland soils for decades and are difficult to remove by management (Coad, Burkitt, Dougherty, & Sparrow, 2014;Falkengren-Grerup et al, 2006). Finally, these grazed Australian temperate grasslands generally move from dominance by C 4 (usually Themeda triandra Forssk.)…”
mentioning
confidence: 99%
“…For example, in addition to predicting the rate of decline in WEP was a function of Olsen P and ASC, Dodd et al (2013) investigated further using 33 P to show that the rate of decline in WEP was associated with P that was immediately exchangeable, while more strongly sorbed P only exchangeable over months was not. In measuring CaCl 2 -P in six Australian soils of varying soil P sorption capacity, Coad et al (2014) found that the rate of decline in CaCl 2 -P over 4 years was inversely related to soil P sorption capacity, measured as the P buffering index (Burkitt et al, 2006). Calcium chloride extractable P was used in this study a proxy to estimate the potential for P loss in leachate (McDowell and Condron, 2004).…”
Section: Variation In the Rate Of Olsen P And Wep Declinementioning
confidence: 98%
“…The most extreme version of a negative P balance involves no application or returns of P to the soil. Research has shown that in grassland systems with little erosion and a similar climate this no-P scenario results in a rate of decline that reflects the initial STP concentration and ASC (Dodd et al, 2013;Coad et al, 2014). Other management strategies are available to decrease P losses while improving the chances of being profitable.…”
Section: Introductionmentioning
confidence: 99%